2013
DOI: 10.1530/eje-12-0981
|View full text |Cite
|
Sign up to set email alerts
|

TSH and free triiodothyronine concentrations are associated with weight loss in a lifestyle intervention and weight regain afterwards in obese children

Abstract: Objective: The impact of thyroid hormones on weight loss in lifestyle interventions and on weight regain afterwards is unknown. Therefore, we studied the relationships between TSH, free triiodothyronine (fT 3 ), free thyroxine (fT 4 ), and weight status, as well as their changes during and after a lifestyle intervention in obese children. Materials and methods: We evaluated the weight status as BMI-SDS in 477 obese children (mean age 10.6G2.7 years, 46% male, mean BMI 28.1G4.5 kg/m 2 ) participating in a 1-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 35 publications
5
69
0
Order By: Relevance
“…This result may be the reason why the studied biochemical parameters remained unchanged overall (Table 4). Like several other studies (4,13,14,17,30) we did not find an association between BMI-SDS variation and TSH, even after substantial weight loss (BMI-SDS variation ≤ -0.5).…”
Section: δBmc-sdssupporting
confidence: 68%
“…This result may be the reason why the studied biochemical parameters remained unchanged overall (Table 4). Like several other studies (4,13,14,17,30) we did not find an association between BMI-SDS variation and TSH, even after substantial weight loss (BMI-SDS variation ≤ -0.5).…”
Section: δBmc-sdssupporting
confidence: 68%
“…One of these studies that stringently corrected for age, smoking habits and menopausal status indicated that for every unit increase in log TSH, there was 2.3 kg greater weight in females and 1.1 kg in men [50]. Conversely, substantial weight loss appears to be associated with a decrease in TSH levels as shown in several studies in children and adolescents, and also in adults following bariatric procedures such as gastric banding or gastric bypass surgery [51,52,53,54]. Currently there have been no randomised trials of the impact of L -thyroxine therapy in patients with obesity-related elevation of TSH serum levels.…”
Section: Who To Treat/who To Observe: Younger Adults (<65-70 Years)mentioning
confidence: 99%
“…Currently there have been no randomised trials of the impact of L -thyroxine therapy in patients with obesity-related elevation of TSH serum levels. However, as observational studies are consistent in showing that TSH levels revert to normal upon weight reduction [51,52,53,54], a causal relation between SCH and obesity is not anticipated.…”
Section: Who To Treat/who To Observe: Younger Adults (<65-70 Years)mentioning
confidence: 99%
“…In contrast, other studies failed to confirm the association between SCH and obesity [131,144]. Furthermore, as the TSH level in obese children tends to decrease with weight loss from lifestyle changes [150,151,152] and levothyroxine treatment in children with hypothyroidism is associated with minimal change in BMI [153], it is thought that the mildly elevated TSH is the consequence of obesity rather than the cause [154]. …”
Section: Sch In Childhoodmentioning
confidence: 99%